DECISION SUPPORT SYSTEM FOR SELECTING MOBILE LEGENDS HEROES IN EPIC TIER USING AHP-TOPSIS METHOD - Akhmad Zaenal Abidin; Muhammad Fairuzabadi; Wibawa (CV. Fahr Publishing, 2024)
The Mobile Legends game is a Multiplayer Online Battle Arena (MOBA) game designed specifically for mobile phones, though it can also be played on PCs. The game features various roles that players must fill, each with distinct tasks and responsibilities. Not all Mobile Legends players are familiar with these roles, which include core/jungler, roaming, gold lane, mid lane, and exp lane. Choosing heroes in the Epic tier often makes it difficult for players to advance in rank. This tier is considered notoriously challenging by Mobile Legends players because at the season reset, rankings drop from Epic II, Legend, Mythic, and Mythical Glory to Epic V or Epic II. Given these challenges, the author has titled their work